NETosis and Neutrophil Extracellular Traps in COVID-19: Immunothrombosis and Beyond - Zhu, Yuanfeng; Chen, Xiaoli; Liu, Xin (Frontiers in Immunology, 2022)
Infection with SARS-CoV-2, the causative agent of the Coronavirus disease 2019 (COVID-19) pandemic, causes respiratory problems and multifaceted organ dysfunction. A crucial mechanism of COVID-19 immunopathy is the recruitment and activation of neutrophils at the infection site, which also predicts disease severity and poor outcomes. The release of neutrophil extracellular traps (NETs), occurring during a regulated form of neutrophil cell death known as NETosis, is a key effector function that mediates harmful effects caused by neutrophils. Abundant NETosis and NET generation have been observed in the neutrophils of many COVID-19 patients, leading to unfavorable coagulopathy and immunothrombosis. Moreover, excessive NETosis and NET generation are now more widely recognized as mediators of additional pathophysiological abnormalities following SARS-CoV-2 infection. In this minireview, we introduce subtypes of NET-producing neutrophils (e.g., low-density granulocytes), and explain the biological importance of NETs and the protein cargos of NETs in COVID-19. In addition, we discuss the mechanisms by which SARS-CoV-2 causes NETosis by upregulating viral processes (e.g., viral entry and replication) as well as host pro-NET mechanisms (e.g., proinflammatory mediator release, platelet activation, and autoantibody production). Furthermore, we provide an update of the main findings of NETosis and NETs in immunothrombosis and other COVID-19-related disorders, such as aberrant immunity, neurological disorders, and post COVID-19 syndromes including lung fibrosis, neurological disorder, tumor progression and deteriorated chronic illness. Finally, we address potential prospective COVID-19 treatment strategies that target dysregulated NETosis and NET formation via inhibition of NETosis and promotion of NET degradation, respectively.